30.7k views
3 votes
Hey can you please help me posted picture of question

Hey can you please help me posted picture of question-example-1

2 Answers

5 votes
(2x^2+5x+5)(4x-3)=(2x^2)(4x)+(2x^2)(-3)+(5x)(4x)+(5x)(-3)+(5)(4x)+(5)(-3)
(2x^2+5x+5)(4x-3)=8x^(2+1)-6x^2+20x^(1+1)-15x+20x-15
(2x^2+5x+5)(4x-3)=8x^3-6x^2+20x^2+5x-15
(2x^2+5x+5)(4x-3)=8x^3+14x^2+5x-15

Answer: Option C. 8x^3+14x^2+5x-15
User Yuki Inoue
by
5.4k points
6 votes
1. To solve this problem you must apply the proccedure shown below:
2. When you multiply two polynomials, you must apply the distributive property and multiply the coefficients and add the exponents. For example:
(x)(x^2)
The coefficients of both terms are 2 and 4 and the sum of the exponents is 3= (1+2=3)
Therefore:
(2x^2)(4x)=8x^3
3. Keeping that on mind, when you multiply the polynomials shown in the figure attached, the correct answer is the option C.
User Haniku
by
5.8k points